Efeito do déficit hídrico na expressão de pigmentos fotossintéticos em physcomitrium acutifolium broth. (Funariaceae) - (:unkn) unknown (Universidade Federal do Pampa, 2018)
Due to the resilience of bryophytes and their ability to colonize in various types of environmental conditions, the biotechnological studies with in vitro moss aim to unravel the physiological responses to a better understanding of the relation between plant and environment. The water deficit is a factor that causes changes in the physiological processes, being one of them, changes in the expression of the photosynthetic pigments. The objective of this study was to evaluate the response of photosynthetic pigments of Physcomitrium acutifolium Broth. in different water stress conditions. Water stress induction was performed with five concentrations of polyethylene glycol (PEG) combined with two 2 hour and 24 hour stress duration forms on a shaker table with KNOP medium maintained in BOD with photoperiod of 16/8 h ( light / dark) at 20 ± 1.4 ° C. The pigments were extracted with DMSO and 80% acetone and the absorbance measured in UV-VIS SP 2000UV spectrophotometer. DMSO samples were refrigerated for readings after 3 and 7 days. The data were submitted to ANOVA and performed t-Student test and the means compared by the Tukey test in the R Studio software. It was verified that the 80% acetone method had the highest pigment extraction values when compared to the DMSO method, expressing significant differences in water stress of 2 hours and 24 hours, mainly in the P5 treatment (-0.40 Mpa). The DMSO method showed a statistical difference in the 24 hour stress time for chlorophyll a (663), however, it provided more stable values. P. acutifolium showed resilience in the most extreme condition, in this case P5 (-0.40 MPa) in 2 hours, but it was sensitive to 24-hour stress. In general, the pigments obtained a similar behavior, because at the time of stress of two hours in P5, both pigment expressions were more expressive; in contrast, these values decrease in the time of 24 hours under water stress. The readings of the DMSO method to evaluate the storage capacity did not present significant difference between days 1, 3 and 7, except for the wavelength 645 of day 1, that is, the extracts remained stable. Additional studies will be needed to understand the processes involved in the response to water stress of P. acutifolium.
Keywords: Estresse hídrico; Briófita; Espectrofotometria; DMSO; Acetona 80%; Water stress; Bryophyte; Spectrophotometry; 80% acetone; CNPQ::CIENCIAS BIOLOGICAS